Experimental Investigation of Particle Sorting in Y-Channels with Variable Bifurcation Angles for Microfluidic Applications - Khola Ikram; Syed Maaz Hasan; Ch Abdullah; M Zulfiqar; Emad Uddin; Zaib Ali; M. Sajid (Journal of Applied Science and Engineering)
The curvature of microchannels significantly influences the direction and amplitude of secondary flow, impacting particle sorting efficiency. Using an inertia-based microchannel model for particle sorting, a detailed flow characterization analysis was done to identify particle sorting and promote standards methods in the microfluidics field. Bends of various angles have numerous uses in microfluidics, and it is essential to comprehend the flow behavior in these microchannels. This work represents the results of a microchannel analysis with various micro-bend angles. Four microchannel designs were studied with outlet angles of 45◦, 60◦, 90◦, and straight channels. Microchannel was fabricated through SLA 3d printing and laser cutting. To investigate the influence of flow-related parameters on systems performance, testing was conducted using 10 & 20 µm, 20 & 60 µm, and 40 & 60 µm sized particles and flow rates of 50-250 µL/min to stimulate red and white blood cells. Furthermore, imaging was done using a microscope, and postprocessing was done through MATLAB Image Processing. This study reveals that a detailed investigation of particle sorting is necessary to produce consistent test techniques for microfluidic devices to enhance medical diagnostic field performance and promote advancement in the biomedical industry.